Progressive vitiligo with rosette sign under dermatoscope: a case report - Yanfei LI; Qiri MU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
We report a case of progressive vitiligo with rosette sign under dermatoscope. A 58-year-old man complained of white patches on the dorsal hands, scrotum and groin for 3 months. Dermatological examination revealed round or irregularly shaped hypopigmented spots or porcelain white patches with sharp or undefined boundaries on the dorsal hands, scrotum and groin. Dermatoscopic examination showed bright white rosette sign on the white patch of the dorsal hands, and hypopigmentation around hair follicle on the scrotum. After the skin lesions fully developed, the rosette sign on the dorsal hands disappeared. Diagnosis: Vitiligo vulgaris (progressive, sporadic).